High chemoselectivity in the phenol synthesis - Rudolph, Matthias; McCreery, Melissa Q.; Frey, Wolfgang; Hashmi, A. Stephen K. (Beilstein journal of organic chemistry, 2011)
Efforts to trap early intermediates of the gold-catalyzed phenol synthesis failed. Neither inter- nor intramolecularly offered vinyl groups, ketones or alcohols were able to intercept the gold carbenoid species. This indicates that the competing steps of the gold-catalyzed phenol synthesis are much faster than the steps of the interception reaction. In the latter the barrier of activation is higher. At the same time this explains the high tolerance of this very efficient and general reaction towards functional groups.
Gesehen am 21.09.2022